The Total Social Costs of Constructing and Operating a High-Speed Rail Line Using a Case Study of the Riyadh-Dammam Corridor, Saudi Arabia - Almujibah, Hamad; Preston, John (Frontiers in Built Environment, 2019)
Introducing a High-Speed Rail technology between the Saudi Arabian cities starts raising many challenging issues of different nature ranging from technical to operational, which require huge investments in infrastructure, operations and maintenance. Background information about the development of HSR worldwide to date is included. However, the main aim of this paper is to determine a methodology to estimate the full cost of travel and provide insights into the working model developed to include the calculations of the total social costs of building a new HSR line for the Riyadh-Dammam corridor in Saudi Arabia and understand in what circumstances it is a suitable technology to use. The Spreadsheet Total Cost Model (STCM) is used to determine the calculations of operator costs, user costs, and environmental costs. In order to determine the total social costs of proposed HSR line worldwide, the travel demand has to be forecasted. In this paper, the gravity demand model is used as a function of independent variables for the cities alongside with the proposed line such as the population, GDP per capita, the generalized journey time, unemployment rate, years since opening the corridor, and the dummy variable if applicable. As a result of this paper, the total social costs of constructing and operating the proposed HSR line is 1,090,106,913 resulted from the sum of the total operator cost that is valued of €859,797,307 per year, the total user cost of €216,769,247 per year, and the total external environmental cost of €13,540,359 per year. In conclusion, the governments and supranational agencies are usually supporting the investment in HSR infrastructure in order to improve the speed and efficiency of the network overall between cities, provide a better experience for passengers, and increase the economy by creating jobs and wealth in the long term.